Regulating Pornocomic Sales to Juveniles in Japan: Cycles and Path-Dependence of a Social Problem - Akagawa, Manabu (Qualitative Sociology Review, 2015)
The purpose of this paper is to develop a new constructionist perspective on path-dependence of a social problem by examining the process of constructing issues regarding the revisions of the Tokyo Youth Protection Ordinance from December 2008 to July 2010. I start with pointing out that a social problem has a cycle of concern and a unique past and background, in a word, path-dependence. Once a social problem process has started down a track, the costs of reversal are very high. Through investigating the revision process between pro-regulation and anti-regulation groups compared with the previous arguments, I found three characteristics of arguments: the limited use of statistics, shared grounds, and shared warrants. I interpret the features as an unintended consequence of path-dependence of the pornocomic problem. This context limits the course of claims-making activities and affects the following controversy. I conclude that the concept of path-dependence offers a better understanding of how and why claims-making activities sometimes lose their diversity and are lopsided over time.